2012
DOI: 10.1021/jf3011323
|View full text |Cite
|
Sign up to set email alerts
|

Can Agricultural Cultivation Methods Influence the Healthfulness of Crops for Foods?

Abstract: ABSTRACT:The aim of the current study was to investigate if there are any health effects of long-term consumption of organically grown crops using a rat model. Crops were retrieved over two years from a long-term field trial at three different locations in Denmark, using three different cultivation systems (OA, organic based on livestock manure; OB, organic based on green manure; and C, conventional with mineral fertilizers and pesticides) with two field replicates. The cultivation system had an impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Also, for human health biomarkers, e.g. plasma IgG levels, no evidence of higher value from either of the two farming systems were detected [102]. However, some exceptions as to tocopherol contents were noted in the literature: (i) an overall higher content in total tocochromanol content and a change to a higher tocotrienol/tocopherol ratio were found for organically grown barley as compared to conventionally grown barley [96], (ii) higher contents of α-, and γ-tocopherols in organic plums as compared to conventional plums, especially when grown on natural covered meadow soil [100], and (iii) a higher α-tocopherol content in organic pears as compared to conventionally grown pears [101].…”
Section: Comparison Of Compounds In Organic and Conventional Cropsmentioning
confidence: 99%
“…Also, for human health biomarkers, e.g. plasma IgG levels, no evidence of higher value from either of the two farming systems were detected [102]. However, some exceptions as to tocopherol contents were noted in the literature: (i) an overall higher content in total tocochromanol content and a change to a higher tocotrienol/tocopherol ratio were found for organically grown barley as compared to conventionally grown barley [96], (ii) higher contents of α-, and γ-tocopherols in organic plums as compared to conventional plums, especially when grown on natural covered meadow soil [100], and (iii) a higher α-tocopherol content in organic pears as compared to conventionally grown pears [101].…”
Section: Comparison Of Compounds In Organic and Conventional Cropsmentioning
confidence: 99%
“…In one carefully conducted crop production experiment, followed by a rat feeding trial, the production system had an apparent effect on plasma-IgG concentrations but not on other markers of nutritional or immune status [ 56 ]. A two-generational rat study based on feed grown in a factorial design (fertilisation x plant protection) of organic and conventional practices revealed that the production system had an effect on several physiological, endocrine and immune parameters in the offspring [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lauridsen et al compared diets from food products derived from either low fertilizer without pesticides, low fertilizer input with pesticides, or high fertilizer with pesticides and found that serum IgG concentrations were higher in rats from the two low-fertilizer groups than in rats from the high-fertilizer group. In contrast, Jensen et al found that IgG levels were higher in rats eating diets made from conventionally produced crops than from organically produced crops. Other animal studies have observed changes in lymphocyte populations and in lymphocyte function due to cultivation system.…”
Section: Introductionmentioning
confidence: 89%
“…It appears to have arisen from a belief that organically grown foodstuffs have a superior nutrient profile and are healthier than conventionally produced foodstuffs. The belief of “healthiness” of organic foods is a highly controversial topic in the scientific community. Some literature reviews conclude that organically and conventionally produced foodstuffs are broadly comparable in their nutrient profile, whereas others conclude that organic produce has higher levels of nutritionally desirable compounds, as well as lower levels of undesirable compounds. Variation in the nutritional content of foodstuffs have also been found to depend on factors such as harvest year, field location, and time of harvest, and these may be masking the differences between cultivation systems. However, limited research has been performed to study the potential health effects of organic foodstuffs, and reliable physiological markers or biomarkers are needed to measure the influence on health status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation